PENGARUH INDIKATOR KEUANGAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SUB SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2022 - Dwi Marthika, Laula (Universitas La Tansa Mashiro, 2023)
This research aims to determine the effect of liquidity ratios measured by the Current Ratio, solvency ratios measured by the Debt to Equity Ratio, activity ratios measured by Total Asset Turn Over and profitability ratios measured by Net Profit Margin on financial performance measured by Return on Investment in sub-sector companies pharmacies registered on the IDX for the 2017-2022 period. Sampling in this research was carried out using a purposive sampling method, so a sample of 9 pharmaceutical sub-sector companies registered on the IDX for the 2017-2022 period was obtained. Data analysis was carried out using multiple linear regression analysis. The results of research on the financial performance of pharmaceutical companies listed on the IDX for the period 2017 to 2022 show that a high current ratio value does not guarantee the company will quickly pay off its debt obligations. The value of current assets is not necessarily profitable for the company. Effective and efficient management by maximizing the use of company assets will increase sales. This allows the company to generate profits that can be used to improve financial performance. The results of this research can prove that liquidity ratios, solvency ratios, activity ratios and profitability ratios influence financial performance.